2023
DOI: 10.1038/s41598-023-35828-8
|View full text |Cite
|
Sign up to set email alerts
|

Production performance and rumen bacterial community structure of Hu sheep fed fermented spent mushroom substrate from Pleurotus eryngii

Abstract: This study aimed to investigate the effect of fermented spent mushroom substrate from Pleurotus eryngii (SMPE) supplementation on production performance, meat quality and rumen bacterial community structure of Hu sheep. 120 2-month-old Hu sheep with average body weight [(13.50 ± 3.10) kg] were selected and randomly divided into 4 groups with 3 replicates per group and 10 sheep per replicate. The control group (RL1) was fed a total mixed ration (TMR), and group RL2, RL3 and RL4 were fed the basal diets suppleme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Therefore, this experiment evaluated the effect of adding SHMS to goat diets on the amino acid and fatty acid composition of the meat. Previous studies have shown that the addition of fertilized spent mushroom substrate from Pleurotus eryngii to Hu sheep can increase the amino acid content of lamb meat [ 17 ]. In line with the results of this experiment, the addition of SHMS significantly increased the content of histidine and tyrosine in goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this experiment evaluated the effect of adding SHMS to goat diets on the amino acid and fatty acid composition of the meat. Previous studies have shown that the addition of fertilized spent mushroom substrate from Pleurotus eryngii to Hu sheep can increase the amino acid content of lamb meat [ 17 ]. In line with the results of this experiment, the addition of SHMS significantly increased the content of histidine and tyrosine in goats.…”
Section: Discussionmentioning
confidence: 99%
“…The dietary composition is a crucial factor affecting the rumen microbiota, and changes in these nutrients can impact the structure of the rumen microbiota community [ 16 ]. In a previous study, it was found that adding a certain proportion of the fermented spent mushroom substrate from Pleurotus eryngii to the diet of Hu sheep increased the diversity of the rumen microbiota and altered the microbial community’s structure [ 17 ]. However, research on the impact of the spent mushroom substrate on the rumen microbiota of ruminants is limited, and there is a lack of studies on the application of composite alkali-stored SHMS in ruminant nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Kim et al (2011) indicated that 10% fermented oyster mushroom residue in the diet could enhance Holstein calves’ growth performance and blood biochemical indicators were not affected. Huang et al (2023) found that the incorporation of 15% Pleurotus eryngii fermentation residues in Hu sheep diets had the best effect on improving production performance, rumen microbial composition, and rumen microbial abundance of Hu sheep. Mandale et al (2023) considered that supplementing 10% mushroom residues in Berari goat diets could reduce feed costs and improve growth performance in Berari goats.…”
Section: Introductionmentioning
confidence: 94%